On-chip phenotypic analysis of inflammatory monocytes in atherogenesis and myocardial infarction - Foster, Greg A. (National Academy of Sciences, 2013)
Monocyte recruitment to inflamed arterial endothelium initiates plaque formation and drives progression of atherosclerosis. Three distinct monocyte subsets are detected in circulation (CD14(++)CD16(−), CD14(++)CD16(+), and CD14(+)CD16(++)), and each may play distinct roles during atherogenesis and myocardial infarction. We studied a range of subjects that included otherwise healthy patients with elevated serum triglyceride levels to patients presenting with acute myocardial infarction. Our objective was to correlate an individual’s risk with the activation state of each monocyte subset as a function of changes in adhesion receptor expression using flow cytometric quantitation of integrins and l-selectin membrane expression. A microfluidic-based laboratory-on-a-chip was developed to quantify the adhesion efficiency of monocytes sheared in whole blood on vascular cell adhesion molecule-1, while characterizing adhesion receptor expression and topography on captured monocytes. CD14(++)CD16(+) monocytes adhered with sevenfold higher efficiency than other subsets, and in patients with myocardial infarction the capture efficiency of this subset was double that for healthy subjects. In patients with hypertriglyceridemia, this increase in monocyte adhesion was attributable to CD14(++)CD16(+) uptake of triglyceride-rich lipoproteins and subsequent signaling via a Phospholipase C–dependent mechanism to increase CD11c expression, very late antigen–4 function, and integrin coclustering within focal adhesive sites on vascular cell adhesion molecule-1. In summary, we introduce a unique laboratory-on-a-chip method for quantifying the activation state of monocyte subsets. These experiments reveal that CD11c/CD18 is an inducible integrin whose expression correlates with a monocyte inflammatory state in subjects at risk for atherogenesis and in patients with myocardial infarction.